2011
DOI: 10.1093/infdis/jir688
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination With Parenteral Toxoid B Protects Hamsters Against Lethal Challenge With Toxin A–Negative, Toxin B–Positive Clostridium difficile but Does Not Prevent Colonization

Abstract: Toxin A has historically been regarded as the primary virulence determinant in Clostridium difficile infection, but naturally occurring toxin A-negative, toxin B-positive (A-/B+) C. difficile strains are known to be virulent. To determine the role of toxin B in these strains, we immunized hamsters with a toxoid prepared from purified toxin B to determine whether they would be protected from lethal challenge with an A-/B+ strain of C. difficile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…Toxoids TcdA and TcdB, generated by formalin inactivation of holotoxins, represent the major focus of vaccine development and have been tested in patients (1,19,29,50,51). Recent studies in patients (36) and in animal models (30,41) have highlighted the relative importance of TcdB as one of the primary virulence factors in CDI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Toxoids TcdA and TcdB, generated by formalin inactivation of holotoxins, represent the major focus of vaccine development and have been tested in patients (1,19,29,50,51). Recent studies in patients (36) and in animal models (30,41) have highlighted the relative importance of TcdB as one of the primary virulence factors in CDI.…”
Section: Resultsmentioning
confidence: 99%
“…In support of this notion, antibodies against both toxins are protective in hamsters (13,28,34), and serum anti-Tcd antibodies in patients correlate with protection against symptomatic disease and recurrence (31,33). Vaccine candidates that target the C. difficile toxins include toxoids (1,16,18,50,51,56) and recombinant TcdA RBD fragments (4, 15, 43, 46-48, 59, 60). Toxoids, generated by formalin inactivation of holotoxins, represent the major focus of vaccine development and have been tested in patients (1,19,29,51).…”
mentioning
confidence: 98%
“…Vaccines targeting the C. difficile toxins include toxoids [19][20][21][22][23] and toxin fragments. [24][25][26][27][28][29] Formaldehyde-inactivated native C. difficile toxins have been reported to be well tolerated and able to induce protective immunity in CDI in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Torres et al found that a combination of parenteral and mucosal toxoid immunization protected hamsters from CDI (11), and in humans, toxoid immunization induced an anti-toxin Ab response that correlated with decreased recurrent CDI (12,13). However, toxoid vaccination does not affect colonization (14). Because no vaccine for CDI is available, we think that an important step in developing a vaccine is to fully understand the nature of protective immune responses to C. difficile.…”
mentioning
confidence: 99%